Nanoscale stiffness topography reveals structure and mechanics of the transport barrier in intact nuclear pore complexes - Bestembayeva, Aizhan (Nat Nanotechnol, 2014)
The nuclear pore complex (NPC) is the gate for transport between the cell nucleus and the cytoplasm. Small molecules cross the NPC by passive diffusion, but molecules larger than ~5 nm must bind to nuclear transport receptors to overcome a selective barrier within the NPC(1). Whilst the structure and shape of the cytoplasmic ring of the NPC are relatively well characterized(2-5), the selective barrier is situated deep within the central channel of the NPC and depends critically on unstructured nuclear pore proteins(5),(6), and is therefore not well understood. Here, we show that stiffness topography(7) with sharp atomic force microscopy tips can generate nanoscale cross sections of the NPC. The cross sections reveal two distinct structures, a cytoplasmic ring and a central plug structure, which are consistent with the three-dimensional NPC structure derived from electron microscopy(2-5). The central plug persists after reactivation of the transport cycle and resultant cargo release, indicating that the plug is an intrinsic part of the NPC barrier. Added nuclear transport receptors accumulate on the intact transport barrier and lead to a homogenization of the barrier stiffness. The observed nanomechanical properties in the NPC indicate the presence of a cohesive barrier to transport, and are quantitatively consistent with the presence of a central condensate of nuclear pore proteins in the NPC channel.